Effects of polyphenol consumption on recovery in team sport athletes of both sexes: A systematic review - Sánchez Díaz, M.; Martín-Castellanos, A.; Fernández-Elias, V. E.; Lopéz Torres, O.; Calvo, J. L. (Nutrients, 2022)
Previous studies have shown that polyphenol consumption enhances recovery of the muscle after exercise-induced muscle damage (EIMD). However, EIMD markers have not been studied by sport type. The main aim of this research was to perform a systematic review to determine the efficacy of polyphenolic consumption in increasing muscle recovery for performing team sport skills. Eligible studies included, following PICOS structure, presented at least one of the following outcomes: maximal isometric voluntary contraction (MVIC); countermovement jump (CMJ); delayed onset muscle soreness (DOMS); 20 m sprint test; creatine kinase (CK); and C-reactive protein (hsCRP). A structured search was carried out following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The risk of bias was assessed using the PEDro scale tool. The review showed a possibly positive impact of polyphenol consumption on recovery after EIMD in team sports athletes. No differences were found between sexes. Considering the limitations, there is moderate to very low certainty of polyphenol supplementation effects on recovery of team sport females and males. A dose of 60 mL/day, divided into two times per day, ingested for >7 days may present positive effects on muscle function and muscle soreness in team sport athletes. However, further investigation is required, specifically in females.